Methods and data sources for identifying members of a regulated community. Issue 1 (23rd July 2015) - Pittman, William C.; Han, Zhe; Harding, Brian Z.; Jiang, Jiaojun; Rosas, Camilo; Pineda, Alba; Mannan, M. Sam
Abstract : The Ammonium Nitrate explosion that shook West, Texas in April 2013 revealed deficiencies in the current regulatory enforcement system used for chemical safety and security in the United States. This cannot be said to be a failure of existing regulations. Rather, it is a failure in enforcement as federal regulators either had not inspected the site in decades—as with OSHA—or had not been aware of its existence at all, as with Department of Homeland Security (DHS). Regulations cannot be effective if they are not enforced and cannot be enforced unless the regulator knows who the members of the regulated community are. Methods for identifying the regulated community and moving past the voluntary reporting and compliance system currently in place have become topics of acute interest and paramount importance. This article discusses existing data sources at federal, state, and local levels that could be exploited immediately to help DHS and other regulators identify regulated facilities and begin more concerted outreach programs. © 2015 American Institute of Chemical Engineers Process Saf Prog 35: 47–52, 2016